Effects of light, temperature and feeding on growth of artificially propagated corals Dipsastraea pallida (DANA, 1846) and Dipsastraea speciosa (DANA, 1846) - Lim, Saoi May (2018)
This study examines the parameters that influence the growth of turbid water coral; Dipsastraea pallida and Dipsastraea speciosa from Tanjung Tuan, Port Dickson including variances in light intensity, temperature and feeding, to generate turbid water coral aquaculture protocol for conservation purposes. Dipsastraea pallida and D. speciosa were subjected to six different light treatments under LED and fluorescent lights, showed better growth under light intensity at 60 μmol m-2 s-1. At this light intensity, D. pallida recorded highest specific growth rate (SGR), which were 1.66 ± 0.15 mg week-1 under LED and 1.65 ± 0.18 mg week-1 under fluorescent lights, while Dipsastraea speciosa reached 1.65 ± 0.16 mg week-1 (LED) and 1.63 ± 0.16 mg week-1 (fluorescent) respectively. Coral specimens were tested for thermal tolerance with increasing temperature up to bleaching point. Results showed Dipsastraea pallida and D. speciosa can withstand temperature up to 34 °C for five days continuously and bleached once exposed to 35 °C and do not recover from bleaching. Artemia sp. nauplii were fed to D. pallida and D. speciosa to examine the optimal feeding time and feeding rate. Both species presented diurnal feeding behavior with highest feeding rate in the afternoon from 1200h to 1400h, with preferable feeding density of Artemia sp. nauplii at 5 ind mL-1 with average 107.20 ± 2.47 ind-1 polyp-1 h-1 (D. pallida) and 113.60 ± 3.59 ind-1 polyp-1 h-1 (D. speciosa). Present study concludes that D. pallida and D. speciosa from Tanjung Tuan exhibit diurnal feeding behavior. Result showed evident showed that these two species have adapted to Tanjung Tuan low light water conditions with better growth performance at light intensity 60 μmol m-2 s-1. These two species from the intertidal zone have higher heat tolerance with bleaching point at 35 °C.